Ruthenium based antimicrobial theranostics – using nanoscopy to identify therapeutic targets and resistance mechanisms in Staphylococcus aureus. Issue 1 (6th November 2019) - Smitten, Kirsty L.; Fairbanks, Simon D.; Robertson, Craig C.; Bernardino de la Serna, Jorge; Foster, Simon J.; Thomas, Jim A.
Abstract : A detailed study on the uptake and antimicrobial activity of a Ru II theranostic complex with wild-type S. aureus, MRSA, and other mutants has identified the specific resistance mechanisms that Gram-positive bacteria display against this lead. Abstract : In previous studies we reported that specific dinuclear Ru II complexes are particularly active against pathogenic Gram-negative bacteria and, unusually for this class of compounds, appeared to display lowered activity against Gram-positive bacteria. With the aim of identifying resistance mechanisms specific to Gram-positive bacteria, the uptake and antimicrobial activity of the lead complex against Staphylococcus aureus SH1000 and other isolates, including MRSA was investigated. This revealed differential, strain specific, sensitivity to the complex. Exploiting the inherent luminescent properties of the Ru II complex, super-resolution STED nanoscopy was used to image its initial interaction with S. aureus and confirm its cellular internalization. Membrane damage assays and transmission electron microscopy confirm that the complex disrupts the bacterial membrane structure before internalization, which ultimately results in a small amount of DNA damage. A known resistance mechanism against cationic antimicrobials in Gram-positive bacteria involves increased expression of the mprF gene as this results in an accumulation of positively charged lysyl-phosphatidylglycerol on the outer leaflet of the cytoplasmic membrane that electrostatically repel cationic species. Consistent with this model, it was found that an mprF deficient strain was particularly susceptible to treatment with the lead complex. More detailed co-staining studies also revealed that the complex was more active in S. aureus strains missing, or with altered, wall teichoic acids.